Glass-ceramic: Controlled crystallization of glasses obtained from biomass ash - Dias, Thais Samira Souza [UNESP]; Leme, Thariany Sanches [UNESP]; dos Santos, Luiz Fernando [UNESP]; Magalhães, Renata da Silva [UNESP]; de Almeida Santos, Gleyson Tadeu [UNESP]; Teixeira, Silvio Rainho [UNESP]; de Souza, Agda Eunice [UNESP] (Wiley, 2023)
In this work, vitreous material was produced, using ash from burning wood in a boiler, to obtain a glass-ceramic with the gehlenite phase. The glass obtained by melt-quenching at 1450°C was characterized by differential scanning calorimetry and other techniques to determine the glass transition and crystallization temperatures, and crystallization kinetics were investigated using the Kissinger model. Tablets prepared with glass powder were treated at 970, 990, 1074, and 1120°C for 1 h, to obtain the glass-ceramic material. The phase identified by X-ray diffraction was gehlenite, with two crystalline structures coexisting in the sample. According to the kinetics study, the phase with a tetragonal structure had a lower crystallization activation energy, and therefore, it may have been the first phase to be formed in the material. Scanning electron microscopy images revealed crystalline regions within the glassy matrix with a lamellar microstructure, with no geometrically defined morphology and no morphological or microstructural distinction, suggesting that both gehlenite phases coexist without apparent distinctions in the glass-ceramic. The best results for water absorption, apparent porosity, and apparent density were for the glass-ceramic sample sintered at 990°C, whose values were respectively 0.1, 0.29, and 2.89 g/cm3.
Keywords: boiler ash; crystallization; glass; glass-ceramics